A user-centred approach to design Transport Interchange Hubs (TIH): A discussion illustrated by a case study in the Russian Arctic - Bleil de Souza, Clarice; Dunichkin, Ilya V.; Pezzica, Camilla (Springer, 2019)
This paper proposes a user-centred approach to design Transport In-terchange Hubs (TIH). It is based on a literature review of existing information related to TIHs outside the domain of transport engineering, so the focus is on the building and the usage of it by its main customers: the travellers. A literature review is used to extract high level information on travellers’ needs, technical and functional requirements of TIHs, constraints and design parameters. A prod-uct development approach is used to classify and combine this data so a proper set of design specifications to better address users’ needs is proposed. The method is illustrated through an example in the Russian Arctic, an area with un-der-developed transport facilities for travellers which would benefit from high-level design specifications to address complex needs, requirements and parame-ters involved in designing for extreme climate conditions. A proof of concept, using Axiomatic Design, to develop design specifications and manage constraints is applied and discussed considering major needs involved in building in the Rus-sian Arctic including how different types of simulation tools, essential to assess performance of complex buildings, can be integrated in the early stages of the design workflow. Robust specifications, despite being part of parametric design methods, are underexplored in the architecture design domain, meaning this work can contribute to further research in how to define common design targets and objectives for different stakeholders as well as to manage the collaborative work of consultants involved in designing complex buildings.